Molecular Diagnosis of Inherited Coagulation and Bleeding Disorders - Bastida, José María; Benito, Rocío; Lozano, María Luisa; Marín-Quilez, Ana; Janusz, Kamila; Martín-Izquierdo, Marta; Hernández-Sánchez, Jesús; Palma-Barqueros, Veronica; Hernández-Rivas, Jesús María; Rivera, José; González-Porras, José Ramón (Seminars in Thrombosis and Hemostasis, 2019)
Diagnosis of inherited bleeding disorders (IBDs) remains challenging, especially in the case of inherited platelet disorders, due to the heterogeneity of the clinical and laboratory phenotype, the limited specificity of platelet function tests, and the large number of potential culprit genes. Unraveling the underlying molecular defect provides the definitive diagnosis of IBDs, facilitating prognosis and clinical care, which are especially important for severe clinical syndromes and those that may be associated with an increased risk of malignancy. Until recently, Sanger sequencing of candidate genes has been the only method of molecular diagnosis, but this approach is time-consuming and costly and requires phenotype-based identification of any obvious candidate gene(s). Nowadays, high-throughput sequencing (HTS) allows the simultaneous and rapid investigation of multiple genes at a manageable cost. This HTS technology that includes targeted sequencing of prespecified genes, whole-exome sequencing, or whole-genome sequencing, is revolutionizing the genetic diagnosis of human diseases. Through its extensive implementation in research and clinical practice, HTS is rapidly improving the molecular characterization of IBDs. However, despite the availability of this powerful approach, many patients still do not receive a diagnosis. As IBDs are complex and rare diseases, development of more advanced laboratory assays, improvements in bioinformatic pipelines, and the formation of multidisciplinary teams are encouraged to advance our understanding of IBDs.
Keywords: molecular diagnosis; inherited platelet disorders; inherited rare bleeding disorders; high-throughput sequencing